STUDI EMPIRIS PENGARUH REPUTASI KAP, OPINI AUDITOR DAN AUDIT TENURE TERHADAP KETERLAMBATAN PENYAMPAIAN LAPORAN KEUANGAN AUDITAN PADA EMITEN PERTAMBANGAN YANG LISTING DI BURSA EFEK PERIODE 2015 – 2018 - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The purpose of this study is to examine the effect of the reputation of the public accounting firm, auditor's opinion, and audit tenure on the delay in the submission of audited financial statements. The data is taken from the Indonesia Stock Exchange for mining companies for the period 2015 - 2018. The data were analyzed using multiple linear regression and tested using the t test and f test. The results of hypothesis testing conclude that the reputation of the public accounting firm partially has a significant negative effect, the auditor's opinion partially has a significant negative effect, audit tenure partially has no effect on the delay in the submission of audited financial statements. While the three independent variables simultaneously have a significant positive effect on the delay in submitting audited financial statements